A photo for Greta - Alter, Anna, 1974- (New York : Knopf, 2011)
Greta's father is a professional photographer who is often away from home, but when he and Greta are together they share wonderful times. Includes activities.
3.7
K-3
K-3
Keywords: Fathers and daughters -- Juvenile fiction; Photographers -- Juvenile fiction; Fathers and daughters -- Fiction; Photographers -- Fiction; Father-daughter relationship -- Fiction; Photographers -- Fiction; Picture books for children